Lifestyles characterization in hypertensive patients of the doctor´s office 7 area IV. Cienfuegos, 2021 - Lianet Pérez Rodríguez; Grissel Utrera Díaz; Laritza Rodríguez Martínez (Medisur)
Background: high blood pressure is considered one of the three most relevant risk factors for cardiovascular and cerebrovascular diseases. Healthy lifestyles prevent its damage. Objective: to characterize the hypertensive patients’ lifestyles in the doctor´s office 7 from area IV of the Cienfuegos’ municipality. Methods: a descriptive, cross-sectional study that included 125 average adult hypertensive patients (30-59 years old), 65 male and 60 female, who met the inclusion criteria. The variables age, skin color, marital status, schooling, personal and family pathological history, eating habits and toxic habits were analyzed. Results: hypertensive, male, non-white skin color and obese patients aged 50 to 59 years predominated; In terms of marital status, the stable union was more frequent and there were no differences in terms of education level. Hypercholesterolemia and arterial hypertension in first-degree relatives, mainly mothers and grandparents, were the most prominent factors among the health history. Inadequate eating habits and toxic habits were the most relevant in the patients under study. Conclusions: the lifestyles of the hypertensive patients who participated in the study are unhealthy and inadequate; there were no differences in terms of sex.